Evaluation of Scintillation Counter Detector Using Gamma Radiation for Gold Detection - Julia Ragab Khalil; Wael Hessen Alawad; Adil Elrayah; Ali Sulaiman Mohamed; Mubark Dirrar Abdallah; Azher S Barrak (Journal of Techniques)
The aim of this work is to evaluate the efficiency of a new gamma spectrometer technology using a scintillation counter detector. This technique can detect the backscattered gamma radiation emitted from the samples. All rock samples were collected and irradiated by two gamma sources, Co60 and Cs137. The existence of gold (Au) was confirmed by displaying the spectrum of one standard made of pure gold and comparing the coincidence of their peaks with that of the rock samples. The spectrum of samples was displayed using the Cassy lab software program. The results indicated that Cs137 gamma spectra showed the same peak for the gold element, while the Co60 gamma spectra indicated the existence of gold radiation. Then, an energy dispersive X-ray (EDX) was done to compare and verify all results.